2014
DOI: 10.31387/oscm0130083
|View full text |Cite
|
Sign up to set email alerts
|

Risks and Risks Mitigations in the Supply Chain of Mangosteen: A Case Study

Abstract: Mangosteen (Garcinia mangostana L.) is the highly demanded fruit for export commodity from Indonesia. The biggest mangosteen production center in Indonesia is West Java Province. The development of the mangosteen supply chain in Indonesia, particularly in West Java Province is heavily affected by uncertain potential risks for the chain. This paper identifies potential risks of the supply chain and studies the interrelationships between strategies for mitigating those risks. Fuzzy Analytical Hierarchy Process (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 30 publications
1
13
0
1
Order By: Relevance
“…The problems identified in this study support the findings revealed in the literature (e.g., Birou & Fawcett, 1993;Klassen & Whybark, 1994;Fawcett, et al, 2008;Colicchia et al, 2010;Cheng et al, 2012;Astuti et al, 2013). Though the respondents didn't cite training in global supply chain management as a problem during the interview, one respondent stated after the interview that the problem of top management not involving procurement and supplies personnel when buying capital goods is a clear picture of the level of training and lack of recognition of procurement at the strategic level of the organisation.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…The problems identified in this study support the findings revealed in the literature (e.g., Birou & Fawcett, 1993;Klassen & Whybark, 1994;Fawcett, et al, 2008;Colicchia et al, 2010;Cheng et al, 2012;Astuti et al, 2013). Though the respondents didn't cite training in global supply chain management as a problem during the interview, one respondent stated after the interview that the problem of top management not involving procurement and supplies personnel when buying capital goods is a clear picture of the level of training and lack of recognition of procurement at the strategic level of the organisation.…”
Section: Resultssupporting
confidence: 81%
“…The findings are additional to the global supply chain problems addressed by other authors (e.g., Dornier et al, 1998;Manuj & Mentzer, 2008;Barry, 2004, Colicchia et al, 2010Cheng et al, 2010;Astuti et al, 2013). Also, the study has managerial implications for the practitioners.…”
Section: Conclusion and Recommendationsmentioning
confidence: 52%
See 2 more Smart Citations
“…Shifting from national underachievement towards international competitiveness requires time and a thorough process of structural change, investments in infrastructure and a new vision which implies collaborative forms, benefits and risk sharing for those who work in the industry as suggested by Beske (2013) and Astuti, Arkeman, Poerwanto and Meuwissen (2013). Meanwhile all supply chain links must improve individual performance by setting up, measuring and analysing results achieved for the six proposed indicators in order to assess progress and performance development on economic and social level as well as within their own supply chain as confirmed by Garcia (2012).…”
Section: Discussionmentioning
confidence: 99%